Preferences of Generation Z in Participating in Cultural Activities in Kuching, Malaysia - Shaik Azahar, Shaik Hussain; Olivia Erina, Petrus; M. D., Dhamalova; Eugen, Popescu; V. M., Ristanovic (2025)
The global tourism industry is increasingly focused on understanding Generation Z (Gen Z), defined as individuals born between 1997 and 2012, due to their distinct characteristics shaped by digital immersion (Meola, 2023; Pew Research Center, 2019). Their preferences, heavily influenced by social media and technology, present new challenges and opportunities for cultural tourism development. Cultural tourism is a significant economic driver, and in Kuching, Sarawak, it is central to the city's identity, promoted through a unique blend of culture, adventure, nature, food, and festivals (CANFF). However, a significant research gap exists regarding the specific cultural activities Gen Z prefers, the factors influencing their participation, and the most effective strategies to promote these activities to them on social media (Robinson & Schanzel, 2019; Vieira et al., 2020; Nguyen et al., 2021).